2020
DOI: 10.3389/fnins.2020.00744
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Transcranial Electrical Stimulation on Human Motor Functions: A Comprehensive Review of Functional Neuroimaging Studies

Abstract: Transcranial electrical stimulation (tES) is a promising tool to enhance human motor skills. However, the underlying physiological mechanisms are not fully understood. On the other hand, neuroimaging modalities provide powerful tools to map some of the neurophysiological biomarkers associated with tES. Here, a comprehensive review was undertaken to summarize the neuroimaging evidence of how tES affects human motor skills. A literature search has been done on the PubMed database, and 46 relative articles were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 100 publications
(166 reference statements)
0
11
0
Order By: Relevance
“…The multimodality of the two offered us valuable information that could not be derived with only one of them. The use of both neuroimaging and neuromodulation is an excellent way to investigate and understand neuromodulation ( Gao et al, 2020a ). However, here, we only report the observation of the cortical activation changes via neuroimaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multimodality of the two offered us valuable information that could not be derived with only one of them. The use of both neuroimaging and neuromodulation is an excellent way to investigate and understand neuromodulation ( Gao et al, 2020a ). However, here, we only report the observation of the cortical activation changes via neuroimaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, here, we only report the observation of the cortical activation changes via neuroimaging. Closer and more in-depth combination of the two could help boost the effect of the neuromodulation, such as a neurofeedback loop and personalized tES ( Gao et al, 2020a ). Through these applications, the parameters of the neuromodulation could be regularized by the information from the neuroimaging technique.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic searches with the keyword of (deep transcranial magnetic stimulation OR dTMS OR repetitive transcranial magnetic stimulation OR rTMS OR TMS OR non-invasive brain stimulation OR theta burst stimulation OR transcranial direct current stimulation OR TBS OR tDCS OR vagus nerve stimulation OR vagal nerve stimulation OR tVNS OR nVNS OR VNS OR static magnetic field stimulation) AND (skill OR professionalism OR skill acquisition) AND (surgery OR surgical OR surgeon) AND (random OR randomized OR randomised) in the PubMed, Embase, ClinicalKey, Cochrane CENTRAL, ProQuest, ScienceDirect, Web of Science, and ClinicalTrials.gov platforms through 19 April 2021 had been conducted (the detailed search strategy is provided in Table S2). Furthermore, to expand the pool of potential studies, we consulted the reference lists of review articles and performed further manual searches [27][28][29]. No language restriction had been applied.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that stimulation-induced alterations in corticospinal excitability are associated with more widespread changes in the sensorimotor network ( Lang et al, 2005 ; Jang et al, 2009 ; Stagg et al, 2009 ; Gao et al, 2020 ). Non-invasive transcranial stimulation of the M1-HAND results in stronger functional coupling between the SMA and the sensorimotor cortex ( Lee et al, 2003 ) and leads to increased regional activity in the SMA ( Jang et al, 2009 ; Stagg et al, 2009 ; R Core Team, 2017 ; Voroslakos et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%